Koreksi Fiskal Laporan Keuangan Koperasi dalam Menentukan Pajak Penghasilan Badan Terutang - Dindin Burhanudin; Cyntia Trisnalianti (J-Coop : Journal of Co-operative, 2025)
This study aims to analyze the compliance of the fiscal financial statements of Koperasi Konsumen Persatuan Wanita Cikeruh (KKPWC) with prevailing tax regulations, to calculate the corporate income tax payable based on fiscal adjustments, and to examine the accounting treatment of the resulting tax obligations. KKPWC is a consumer cooperative operating two business units—savings and loan, and retail—that has been confirmed as a corporate taxpayer. This research employs a descriptive qualitative method with a case study approach, utilizing documentation and in-depth interviews for data collection. The findings reveal that KKPWC has not fully implemented fiscal corrections in accordance with Law of the Republic of Indonesia Number 36 of 2008 on Income Tax. Several accounts, such as depreciation, member welfare funds, and donations, were recorded inconsistently from a fiscal standpoint. The fiscal adjustments resulted in corporate income tax payable amounting to IDR 9,125,056 in 2022 and IDR 3,426,871 in 2023. These discrepancies affect other accounts such as tax expenses, tax liabilities, and the allocation of net income (Sisa Hasil Usaha/SHU) to members. The results highlight the importance of accurate fiscal corrections in cooperative financial reporting to enhance tax compliance and institutional accountability.